2003
DOI: 10.1038/sj.pcan.4500657
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases (MMP-2 and -9) and their inhibitors (TIMP-1 and -2) in prostate cancer tissue

Abstract: Matrix metalloproteinases (MMPs) have been implicated in progression and metastases of different tumours. The balance between the MMPs and their natural inhibitors (tissue inhibitors of matrix metalloproteinases; TIMP) seems to be an important factor related to this role. Here, the expression of MMP-2 and -9 along with TIMP-1 and -2 was examined in prostate cancer tissue. A total of 40 radical prostatectomy specimens were embedded in paraffin and immunohistochemical staining was performed to detect MMP-2 and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 32 publications
(25 reference statements)
6
74
1
7
Order By: Relevance
“…Our results are similar to those published by Lichtinghagen et al (2002) (14), who showed MMP-2 underexpression in prostate cancer tissue using RT-PCR. Conversely, they observed higher expression of MMP-2 at the protein level using immunohistochemistry, a result later confirmed by Brehmer et al (15), indicating that there is a discrepancy between the levels of MMP-2 mRNA and protein in prostate cancer.…”
Section: Discussionsupporting
confidence: 55%
“…Our results are similar to those published by Lichtinghagen et al (2002) (14), who showed MMP-2 underexpression in prostate cancer tissue using RT-PCR. Conversely, they observed higher expression of MMP-2 at the protein level using immunohistochemistry, a result later confirmed by Brehmer et al (15), indicating that there is a discrepancy between the levels of MMP-2 mRNA and protein in prostate cancer.…”
Section: Discussionsupporting
confidence: 55%
“…TIMP-1, -2, and -3 mRNA molecules and proteins were detected in human prostate cancer specimens [22,23], and TIMP-1 has been shown in various studies to be downregulated in prostate cancer as compared to normal prostate [22,24]. A study of TIMP-1, -2, and -3 mRNA showed significant reduction of TIMP 2 and 3 in prostate cancer, as well as significant increases in the ratios of MMP-9 to TIMP-1, -2, and -3, and in the ratio of MMP-14 to TIMP-3 [23].…”
Section: Introductionmentioning
confidence: 97%
“…The MMPs ' activities are subject to regulation by tissue inhibitors of metalloproteases (TIMPs) [ 55 ] . An association between MMPs and/or TIMPs expression and parameters indicative of prostate cancer aggressiveness has also been reported.…”
Section: Mmpsmentioning
confidence: 99%